Peran Ganda Perempuan pada Keluarga Masyarakat Petani: Kasus Istri Petani di kecamatan Merapi Selatan Kabupaten Lahat - Qori Kartika; Rabial Kanada (An Nisa'a, 2017)
This study aims to describe women's perception in Lahat city about the concept of gender equality and gender equality (KKG) in the social and cultural realm of society in Merapi Selatan sub-district of Lahat district. This research uses qualitative-phenomenological method. The subject of the study was not determined according to the data requirement. Data collection was done by observation method and. The results can be summarized as follows: (1) the role of farmer's wife in Merapi Selatan sub-district in economic improvement concentrated in agriculture sector. The demands of the wives to meet the family's needs are the same as for men, so they not only stay home to wait and spend their husbands' income from rice fields, kawean (coffee plantations) but also engage in making a living. either through arian (working with pay per day). (2) The participation of wives in improving family welfare in Merapi Selatan sub-district is manifested in three roles both in home environment, in economy, and in society. The role of housewives in South Merapi district because they have to do household chores and supplies for husbands against rice and kawean. They must complete all duties as mothers and wives who are naturally responsible for them and help make a living.